Glucagon-like peptide-1 receptor agonists and type 1 diabetes: a potential game changer? - Resnick, Ortal; Bril, Fernando; Beauchamp, Giovanna (Frontiers in Endocrinology, 2025)
This mini review explores the increasing prevalence of obesity in type 1 diabetes (T1D) and the challenges patients face in achieving optimal glycemic control with current treatments. It discusses the evidence supporting the use of glucagon-like peptide-1 receptor agonists (GLP-1RA) as potential adjunctive therapy in T1D to reduce weight and improve insulin resistance. Potential benefits need to be weighed against the risk of hypoglycemia and lack of long-term data.